2001
DOI: 10.1007/s004240100561
|View full text |Cite
|
Sign up to set email alerts
|

Adult dystrophic (mdx) endplates exhibit reduced quantal size and enhanced quantal variation

Abstract: Examination of miniature endplate potential (MEPP) distributions indicated that the average quantal size is significantly reduced by approximately 44% in young adult mdx mice (5-7 weeks). The average quantum declined further to approximately 37% of non-dystrophic levels in mature (6- to 24-month) mdx mice. Young adult non-dystrophic and mdx endplates and mature non-dystrophic endplates exhibited a linear relationship between the mean and variance of uniquantal MEPP amplitude distributions. Mature mdx endplates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
(68 reference statements)
2
29
0
Order By: Relevance
“…Together, this suggests that the filling state of the SR contributes significantly to the dysregulation [Ca 2ϩ ] rest observed in mdx muscles. Several reports indicate that resting membrane potentials are more positive in mdx muscles fibers than WT (27,(63)(64)(65). We have found that mdx myotubes showed a partial membrane depolarization compared with WT.…”
Section: Trpc1-dependent Casupporting
confidence: 50%
“…Together, this suggests that the filling state of the SR contributes significantly to the dysregulation [Ca 2ϩ ] rest observed in mdx muscles. Several reports indicate that resting membrane potentials are more positive in mdx muscles fibers than WT (27,(63)(64)(65). We have found that mdx myotubes showed a partial membrane depolarization compared with WT.…”
Section: Trpc1-dependent Casupporting
confidence: 50%
“…This is consistent with previous findings that show sodium channels are excluded from developing mammalian NMJs and chick NMJs with no synaptic folds (Bailey et al, 2003). Thus, reduced synaptic folding in dystrophic muscles could contribute to the functional deficits in synaptic transmission in mdx mice (Carlson and Roshek, 2001; Wood and Slater, 1997). Deficits in synaptic transmission are likely to be exacerbated in DMD because of the greater reliance of synaptic transmission on fold maturation in humans (Slater, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The direct alignment between active zones and junctional folds is lost in many neuromuscular synapses in DMD, because the folds are not mature or maintained (Lyons and Slater, 1991). Synaptic transmission becomes more variable with age in the mdx mouse model of DMD (Carlson and Roshek, 2001), and is likely to be more deleterious in DMD patients because of the greater reliability of synapse function on fold maturation in humans (Slater, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism that could account for the increase in miR-206 is the structural denervation known to occur in the mdx diaphragm during muscle regeneration (28). Upon muscle regeneration, the alteration in the structure of the neuromuscular junction (i.e., reduced acetylcholine receptor clustering) is such that there is increased variability in synaptic transmission (8,29). Support for this mechanism comes from a study in which a muscle-specific noncoding transcript (7H4) was cloned from a synaptically enriched cDNA library derived from the rat diaphragm (42).…”
Section: Discussionmentioning
confidence: 99%